1963
DOI: 10.1002/cjce.5450410110
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of suspensions of coal in mineral oil

Abstract: Viscosity data for slurries of five solid particle systems suspended in a mineral oil are presented for solid concentrations up to 50% by volume. At volume concentrations of less than 30% the results are well represented by the Einstein equation in its fluidity form, the constant varying with the system between 2.65 and 3.15, (as compared with 2.5 in the theoretical equation). At higher concentrations the slurries are non‐Newtonian, and no satisfactory correlation is available in this region, very little compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The influence of the particles shape on the bulk viscosity has been studied for low Re number suspensions. [30][31][32] These studies showed that the more the shape of the particle deviated from that of a sphere, the greater was the bulk viscosity. Moreover, aspherical particles demonstrate increased ordering near the walls (an effect which is more pronounced for the smooth walls).…”
Section: -7mentioning
confidence: 99%
“…The influence of the particles shape on the bulk viscosity has been studied for low Re number suspensions. [30][31][32] These studies showed that the more the shape of the particle deviated from that of a sphere, the greater was the bulk viscosity. Moreover, aspherical particles demonstrate increased ordering near the walls (an effect which is more pronounced for the smooth walls).…”
Section: -7mentioning
confidence: 99%
“…Moreland [2] studied the viscosity of suspensions of low volatile bituminous coal in mineral oil. For a solid volume fraction below 0.30, the results were well represented by the Einstein equation for reduced viscosity, whereas at higher concentrations the slurries were non-Newtonian and no satisfactory correlation was found.…”
Section: Introductionmentioning
confidence: 99%
“…Where oil is available near the coal mines, economic advantages are possible because the oil can serve the dual purpose of both fuel and transport medium. Burners using 60 weight % of coal in oil have been developed for blast furnaces (30).…”
Section: By Pipe Linementioning
confidence: 99%
“…In the thirties, several more systems were installed, including a l/i million ton-per-year line to carry rock salt in saturated solution. By 1959, 20 or more pipe lines were carrying 30 million long tons annually of mixtures of phosphate rock, sand, and clay.…”
mentioning
confidence: 99%